SOME RESULTS SELECTION OF BASIL (OCIMUM BASILICUM L.) IN THE CONDITIONS OF THE REPUBLIC OF MOLDOVA - L. Chisnicean (Овощи России, 2019)
Ocimum basilicum L. (common basil) is one of the promising spicy - aromatic and medicinal plants. It is used both in traditional and traditional medicine as an expectorant, anti-inflammatory agent, gastritis, colitis, nephritis, etc. Numerous scientific studies have established that O. basilicum L. essential oil in experimental practice has good antioxidant, antimicrobial, and cytostatic activity. The modern spice market requires a growing variety of forms and varieties of basil for consumption as seasoning and green vegetables. An important place is occupied by raw materials (leaf and herb of basil), in recipes of medicinal and forest teas. Essential oil is used both in the food and in the perfumery – cosmetic industry and pharmaceuticals. Perspectivity in the spice market and its multiple medicinal properties were the reason for the continuation of work on the improvement and creation of new promising varieties of basil, of various uses. A working collection was created, consisting of 34 varieties, forms and nursery of crosses and breeding selections, numbering from 40 to 100 units, on average by year. Five varieties of basil of diverse directions were created and registered in the State Register, both for consumption as seasoning in fresh and dry form, for flavoring edible salt, vinegar and oil, and also as a medicinal raw material for teas. Brief results obtained over 17 years а presented in this paper.